Application of artificial intelligence in the learning management system LMS (MMIT Proceedings, 2025)
This article examines the integration of artificial intelligence into learning management systems (LMS) to enhance the personalization of the educational process. It discusses innovative approaches and develops recommendations that take into account the individual characteristics and needs of learners, ensuring a more flexible, adaptive, and effective organization of educational materials.